Effect of layer stacking sequence on residual compressive strength for hybrid composite plates - Randjbaran, Elias (2013)
An experimental investigation on the effects of layer stacking sequence on response of 6-layer hybrid composite plates under compression after ballistic impact has been conducted. The composite plates consist of two layers of each of Kevlar, carbon, glass fibres as well as epoxy resin and the hardener. The specimens were prepared through hand-lay-up traditional fabrication method. Five groups of hybrid composite materials were fabricated with the different stacking sequences. Stacking sequence and Orientation of them are as follows; Hybrid 1 : [0K/0C/0G/0K/0G/0C]S , Hybrid 2 : [0G/0C/0K/0C/0K/0G]S , Hybrid 3 : [0K/0G/0C/0G/0C/0K]S, Hybrid 4 : [0G/0K/0C/0C/0G/0K]S , and Hybrid 5 : [0K/0C/0G/0G/0C/0K]S. The specimens were undergone ballistic impact testing and then the residual compressive strength was measured. Finally, the best sequence of the layers for producing high resistance polymeric laminated composites was introduced. It was found that the damage characterisation of Hybrid 2 possesses better impact resistance, ability to absorb the energy and penetration compared to the rest of them. Hybrid 3 has the highest compressive energy absorption after ballistic impact. Calculating the energy absorption upon the ballistic impact defines that Hybrid 2 has the maximum amount of 95.2 J. Besides, Hybrid 3 and Hybrid 5 are showing the same close behaviour, which velocity difference of them is 0.55 m/s and the difference of energy absorption is 0.03 J. Compressive energy absorption of the intact and the clean –hole specimens illustrates that Hybrid 4 in both of them has a maximum strength against the compressive force with 2285 and 1940 J respectively. Compressive ballistic energy absorption of the specimens shows that Hybrid 4 has the highest strength in compression after ballistic impact with 1940 J.